Actinomyces and Related Organisms in Human Infections - Könönen E; Wade WG (AMER SOC MICROBIOLOGY, 2022)
Actinomyces israelii has long been recognized as a causative agent of actinomycosis. During the past 3 decades, a large number of novel Actinomyces species have been described. Their detection and identification in clinical microbiology laboratories and recognition as pathogens in clinical settings can be challenging. With the introduction of advanced molecular methods, knowledge about their clinical relevance is gradually increasing, and the spectrum of diseases associated with Actinomyces and Actinomyces-like organisms is widening accordingly; for example, Actinomyces meyeri, Actinomyces neuii, and Actinomyces turicensis as well as Actinotignum (formerly Actinobaculum) schaalii are emerging as important causes of specific infections at various body sites. In the present review, we have gathered this information to provide a comprehensive and microbiologically consistent overview of the significance of Actinomyces and some closely related taxa in human infections.